How pollen tubes fight for food: the impact of sucrose carriers and invertases of Arabidopsis thaliana on pollen development and pollen tube growth - Seitz, Jessica; Reimann, Theresa; Fritz, Carolin; Schröder, Carola; Knab, Johanna; Weber, Walter; Stadler, Ruth (Frontiers in Plant Science, 2023)
Pollen tubes of higher plants grow very rapidly until they reach the ovules to fertilize the female gametes. This growth process is energy demanding, however, the nutrition strategies of pollen are largely unexplored. Here, we studied the function of sucrose transporters and invertases during pollen germination and pollen tube growth. RT-PCR analyses, reporter lines and knockout mutants were used to study gene expression and protein function in pollen. The genome of Arabidopsis thaliana contains eight genes that encode functional sucrose/H+ symporters. Apart from AtSUC2, which is companion cell specific, all other AtSUC genes are expressed in pollen tubes. AtSUC1 is present in developing pollen and seems to be the most important sucrose transporter during the fertilization process. Pollen of an Atsuc1 knockout plant contain less sucrose and have defects in pollen germination and pollen tube growth. The loss of other sucrose carriers affects neither pollen germination nor pollen tube growth. A multiple knockout line Atsuc1Atsuc3Atsuc8Atsuc9 shows a phenotype that is comparable to the Atsuc1 mutant line. Loss of AtSUC1 can`t be complemented by AtSUC9, suggesting a special function of AtSUC1. Besides sucrose carriers, pollen tubes also synthesize monosaccharide carriers of the AtSTP family as well as invertases. We could show that AtcwINV2 and AtcwINV4 are expressed in pollen, AtcwINV1 in the transmitting tissue and AtcwINV5 in the funiculi of the ovary. The vacuolar invertase AtVI2 is also expressed in pollen, and a knockout of AtVI2 leads to a severe reduction in pollen germination. Our data indicate that AtSUC1 mediated sucrose accumulation during late stages of pollen development and cleavage of vacuolar sucrose into monosaccharides is important for the process of pollen germination.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Arabidopsis thaliana; AtSUC1; AtVI2; carbohydrate storage; esculin; pollen tubes; sucrose transporters; vacuolar invertases

Membrane order in pollen tubes-Methodology and unexpected findings - Parmryd, Ingela; Adler, Jeremy; Fritz, Carolin (Biophysical Journal, 2023)
CRIS-Team Scopus Importer:2023-02-24

Plasma membrane and cytoplasmic compartmentalization: A dynamic structural framework required for pollen tube tip growth - Fritz, Carolin; Reimann, Theresa; Adler, Jeremy; Knab, Johanna; Schulmeister, Sylwia; Kriechbaum, Choy; Müller, Sabine; Parmryd, Ingela; Kost, Benedikt (Plant Physiology, 2024)
Rapid, unidirectional pollen tube tip growth is essential for fertilization and widely employed as a model of polar cell expansion, a process crucial for plant morphogenesis. Different proteins and lipids with key functions in the control of polar cell expansion are associated with distinct domains of the plasma membrane (PM) at the pollen tube tip. These domains need to be dynamically maintained during tip growth, which depends on massive secretory and endocytic membrane trafficking. Very little is currently known about the molecular and cellular mechanisms responsible for the compartmentalization of the pollen tube PM. To provide a reliable structural framework for the further characterization of these mechanisms, an integrated quantitative map was compiled of the relative positions in normally growing Nicotiana tabacum (tobacco) pollen tubes of PM domains (i) enriched in key signaling proteins or lipids, (ii) displaying high membrane order, or (iii) in contact with cytoplasmic structures playing important roles in apical membrane trafficking. Previously identified secretory and endocytic PM domains were also included in this map. Internalization of regulatory proteins or lipids associated with PM regions overlapping with the lateral endocytic domain was assessed based on brefeldin A treatment. These analyses revealed remarkable aspects of the structural organization of tobacco pollen tube tips, which (i) enhance our understanding of cellular and regulatory processes underlying tip growth and (ii) highlight important areas of future research.
Created from Fastlane, Scopus look-up

Quantitative Structural Organization of Bulk Apical Membrane Traffic in Pollen Tubes - Grebnev, Gleb; Cvitkovic, Mislav; Fritz, Carolin; Cai, Giampiero; Smith, Ana-Suncana; Kost, Benedikt (Plant Physiology, 2020)
Pollen tube tip growth depends on balancing secretion of cell wall material with endocytic recycling of excess material incorporated into the plasma membrane (PM). The classical model of tip growth, which predicts bulk secretion, occurs apically, and is compensated by subapical endocytosis, has been challenged in recent years. Many signaling proteins and lipids with important functions in the regulation of membrane traffic underlying tip growth associate with distinct regions of the pollen tube PM, and understanding the mechanisms responsible for the targeting of these regulatory factors to specific PM domains requires quantitative information concerning the sites of bulk secretion and endocytosis. Here, we quantitatively characterized the spatial organization of membrane traffic during tip growth by analyzing steady-state distributions and dynamics of FM4-64-labeled lipids and YFP-tagged transmembrane (TM) proteins in tobacco (Nicotiana tabacum) pollen tubes growing normally or treated with Brefeldin A to block secretion. We established that (1) secretion delivers TM proteins and recycled membrane lipids to the same apical PM domain, and (2) FM4-64-labeled lipids, but not the analyzed TM proteins, undergo endocytic recycling within a clearly defined subapical region. We mathematically modeled the steady-state PM distributions of all analyzed markers to better understand differences between them and to support the experimental data. Finally, we mapped subapical F-actin fringe and trans-Golgi network positioning relative to sites of bulk secretion and endocytosis to further characterize functions of these structures in apical membrane traffic. Our results support and further define the classical model of apical membrane traffic at the tip of elongating pollen tubes.
CRIS-Team Scopus Importer:2020-08-14

Testing Pollen Tube Proteins for In Vivo Binding to Phosphatidic Acid by n-Butanol Treatment and Confocal Microscopy - Fritz, Carolin; Kost, Benedikt (Pollen and Pollen Tube Biology, 2020)
The general role of cellular membranes is to provide a barrier and to generate separate reaction spaces. However, additional functions of membrane domains enriched in certain classes of lipids have been discovered, which represent an important area of ongoing research. Such membrane domains can be found in cells at different size scales (e.g., nanodomains, microdomains), represent membrane regions with special physical properties and play important roles in the direct or indirect propagation of signaling processes. Domain formation within the plasma membrane (PM) does not only involve the accumulation of specific lipids, but also the recruitment of specific transmembrane or PM-associated peripheral proteins. Phosphatidic acid (PA) is increasingly recognized as an important signaling lipid and component of PM domains. This lipid is involved in the regulation not only of biotic or abiotic stress responses, but also of pollen tube tip growth and of other forms of polar cell expansion. Although many PA-binding proteins have been characterized, a conserved PA interaction motif could not be identified in these proteins. Consequently, protein binding to PA cannot be predicted based on sequence analysis, but has to be biochemically tested using lipid strip or liposome assays. Although these assays are often informative, they are generally based on the use of artificial model membranes, which compared to natural membranes contain fewer lipid types often at non-physiological concentrations. In this chapter, we describe an alternative in vivo assay that can be employed to analyze protein binding to PA at the PM of normally elongating tobacco pollen tubes. This assay is based on the use of n-butanol (n-ButOH), which inhibits phospholipase D (PLD) and thereby blocks a major biosynthetic pathway that generates PA within the PM from substrates like phosphatidylcholine (PC) or phosphatidylethanolamine (PE). PLD inhibition reduces the PA content of the PM and consequently the level of PM association of PA-binding proteins, which can be analyzed using fluorescence microscopy. Methods enabling n-ButOH treatment of cultured tobacco pollen tubes expressing YFP-tagged PA-binding proteins as well as the quantitative determination of the PM association of these proteins are described.
CRIS-Team Scopus Importer:2020-06-19
Keywords: Confocal microscopy; n-ButOH; Nicotiana tabacum; PA-binding proteins; PM/cytoplasm ratio of fluorescence intensity; Pollen tubes; Stable transformation; Transient transformation; YFP-tagging